A gender agenda for the future of work in a digital age of pandemics: Jobs, skills and contracts - Rachel Verdin; Jacqueline O'Reilly (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2021)
This article provides an exploration of the literature concerning the impacts of digitization and the fourth industrial revolution on the world of work, informed by the experiences of Covid-19 and focusing on the gendered implications. Key threats and opportunities are identified in projections for declining and emerging occupations, considering how women will fare in the workplaces of the future. These trends are discussed in terms of emerging skill gaps and women's positioning to exploit key areas of growth. Alternative forms of employment and atypical workers are creating regulatory gaps, challenging existing social protection systems, with the pandemic again demonstrating the need for interventions. The pandemic has highlighted the need for a specific gender agenda to ensure past progress is not eroded and the opportunities described are taken up.
Keywords: 330